Biocontrol Ability and Mechanism of a Broad-Spectrum Antifungal Strain Bacillus safensis sp. QN1NO-4 Against Strawberry Anthracnose Caused by Colletotrichum fragariae - Xiaojuan Li; Xiaojuan Li; Xiaojuan Li; Miaoyi Zhang; Dengfeng Qi; Dengbo Zhou; Chunlin Qi; Chunyu Li; Siwen Liu; Dandan Xiang; Lu Zhang; Jianghui Xie; et al. (Frontiers in Microbiology, 2021)
Strawberry is a very popular fruit with a special taste, color, and nutritional value. Anthracnose caused by Colletotrichum fragariae severely limits fruit shelf life during post-harvest storage. Use of traditional chemical fungicides leads to serious environment pollution and threatens food safety. Biocontrol is considered as a promising strategy to manage the post-harvest fruit diseases. Here, strain QN1NO-4 isolated from noni (Morinda citrifolia L.) fruit exhibited a high antifungal activity against C. fragariae. Based on its physicochemical profiles and phylogenetic tree of the 16S rRNA sequence, strain QN1NO-4 belonged to the genus Bacillus. The average nucleotide identity (ANI) calculated by comparing two standard strain genomes was below 95–96%, suggesting that the strain might be a novel species of the genus Bacillus and named as Bacillus safensis sp. QN1NO-4. Its extract effectively reduced the incidence of strawberry anthracnose of harvested fruit. Fruit weight and TSS contents were also maintained significantly. The antifungal mechanism assays indicated that the extract of the test antagonist inhibited mycelial growth and spore germination of C. fragariae in vitro. Cells of strain QN1NO-4 demonstrated the cytoplasmic heterogeneity, disappeared organelles, and ruptured ultrastructure. Notably, the strain extract also had a broad-spectrum antifungal activity. Compared with the whole genome of strain QN1NO-4, several functional gene clusters involved in the biosynthesis of active secondary metabolites were observed. Fifteen compounds were identified by gas chromatography–mass spectrometry (GC-MS). Hence, the fruit endophyte B. safensis sp. QN1NO-4 is a potential bio-agent identified for the management of post-harvest disease of strawberry fruit.